A Case of Immune-Related Adverse Events, Including Myasthenia Gravis, Myositis, and Myocarditis, during Avelumab and Axitinib Combination Therapy - Jurii Karibe; Ryohei Horiguchi; Yohei Hanajima; Akihito Hashizume; Daiji Takamoto; Takashi Kawahara; Kimito Osaka; Jun-ichi Teranishi; Naohisa Ueda; Hiroji Uemura (Case Reports in Oncology)
Introduction: Immune checkpoint inhibitors are the mainstay of treatment for unresectable or metastatic renal cell carcinoma (RCC). However, they can cause immune-related adverse events (irAEs), and the management of these irAEs is critical. The combination of myasthenia gravis, myositis, and myocarditis, which are irAEs, is rare, and it has not been reported to occur with avelumab. This report aimed to present a rare case of RCC metastasis that developed irAEs during avelumab and axitinib combination therapy. Case Presentation: A 76-year-old woman who underwent radical nephrectomy for clear cell RCC (pT1bN0M0 Grade 3 INFb) at the age of 67 years presented to our hospital after her family doctor noted a pancreatic tumor. She was diagnosed with pancreatic metastasis of RCC based on histopathological examination, and avelumab and axitinib combination therapy was initiated. She developed irAEs, including myasthenia gravis, myositis, and myocarditis, which were treated with steroid pulse therapy. The patient recovered after treatment and was discharged without sequelae. Conclusion: Myasthenia gravis, myositis, and myocarditis can occur during avelumab and axitinib combination therapy for RCC. Prompt diagnosis, treatment, and collaboration with other departments are extremely important for managing irAEs.